2011
DOI: 10.1080/1360080x.2011.550087
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers' job satisfaction in a public tertiary institution in Singapore: ambivalent and non-ambivalent relationships between job satisfaction and demographic variables

Abstract: Increasing lecturer turnover rates and fewer qualified recruits choosing a career in academia threaten the integrity of the tertiary education system in Singapore. The purpose of this study was to ascertain the relationship between lecturers' job satisfaction levels in a public tertiary institution and selected demographic variables. The study showed that most respondents were ambivalent as to their job satisfaction. There were significant differences in satisfaction levels based on age and job position. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
26
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 22 publications
9
26
0
2
Order By: Relevance
“…The level of job dissatisfaction is similar to the findings in studies done among teachers in Abeokuta [13] and among civil servants from Singapore [14], where 25.7% and 22% of participants were dissatisfied respectively. Studies have identified different levels of job dissatisfaction among other occupational groups in Nigeria which include studies among police officers, teachers, doctors and psychiatrists [15,16,6].…”
Section: Discussionsupporting
confidence: 86%
“…The level of job dissatisfaction is similar to the findings in studies done among teachers in Abeokuta [13] and among civil servants from Singapore [14], where 25.7% and 22% of participants were dissatisfied respectively. Studies have identified different levels of job dissatisfaction among other occupational groups in Nigeria which include studies among police officers, teachers, doctors and psychiatrists [15,16,6].…”
Section: Discussionsupporting
confidence: 86%
“…These findings imply that administrators in higher education institutions might have to vary their management style and motivational strategies to meet the unique needs of different groups of individuals (Paul & Phua, 2011).…”
Section: Practical Implicationsmentioning
confidence: 98%
“…These demographic variables were selected because they have been linked to the job satisfaction of academics in several previous studies (Oshagbemi, 2003;Paul & Phua, 2011;Schulze, 2006). The results of studies examining the relationship between demographic variables and job satisfaction have been fairly inconsistent and therefore, it is difficult to predict the exact direction of the relationship between the two sets of variables.…”
Section: Job Satisfaction and Demographic Variablesmentioning
confidence: 99%
“…As for faculty of age, previous research has found that it found strong relation between age and job satisfaction (Ssesanga & Garrett, 2005;Malik, 2011). According to Gautam, Mandal, and Dalal (2006), Wong and Heng (2009), older faculty to be less satisfied with their jobs than their younger colleagues because of the novelty of their situation (Paul & Phua, 2011). A significant relationship between faculty job satisfaction and discipline were also discovered in this study and supported by the studies of Terpstra and Honoree (2004), Sabharwal and Corley (2009).…”
Section: Discussionmentioning
confidence: 98%